Sporadic duodenal macrogastrinoma: a rare case report - Šimčikas, Dainius; Poškus, Eligijus; Stanaitis, Juozas; Rinkevičiūtė, Ernesta; Tamošiūnas, Algirdas Edvardas; Strupas, Kęstutis (Acta medica Lituanica, 2013)
Gastrinomas are rare neuroendocrine tumors characterized by the secretion of gastrin, which causes hyperchlorhydria, thereby producing the Zollinger-Ellison syndrome. In most cases this syndrome manifests as severe peptic ulcer disease. We are presenting an extremely rare clinical case of sporadic duodenal macrogastrinoma. The patient underwent investigation due to six-year history of epigastric pain, heartburn and episodic diarrhea. Endoscopy, endosonoscopy and histologic examination of biopsy specimens indicated the presence of duodenal gastrinoma with no signs of peptic ulcers. Pyloroduodenal segment including 3.5 cm macrogastrinoma was resected. This case is unique as duodenal gastrinomas are usually very small, up to 1 cm. During the follow up period we observed slowly decreasing hypergastrinemia. Somatostatin receptor scintigraphy, CT and upper GI endoscopy were performed to reveal the reasons, though did not find any abnormalities. 8 months of follow-up did not reveal any progression of the disease. The etiology of slowly decreasing hypergastrinemia remains unclear, controversial and is under investigation.